The Sources of General International Law in the Recent Works of the International Law Commission (Polish Yearbook of International Law, 2021)
The present text describes the attitude toward sources of law in the recent works of the International Law Commission (ILC) on custom, general principles of law, and jus cogens (with special emphasis on reports of the respective special rapporteurs). The three main tasks of the text are to verify whether the ILC rapporteurs: grasped the essence of unwritten sources (reality-concern); preserved the coherence of views when referring to different topics (coherence-concern); and last but not least allow states to have the decisive voice as regards the set of their obligations (sovereignty-concern). The author notes the nominal strict attachment of the ILC to two-element nature of custom as a general practice recognized as law. Though in fact it should be a good message for states, this strict attitude of the ILC seems not to be based on a real stress test. It seems to ignore the reality of lawyers and even international judges referring to several customary norms without the slightest attempt to verify the true existence of both the two elements of custom – namely practice and opinio juris. What is more, the ILC does not see any problem with calling all general principles as sources of law. What is overlooked is the element of state consent to be bound by several presumed general principles. This is qualified by the author as a threat to state sovereignty – with states being pressured to follow some patterns of conduct to which they have not given their consent.